Evaluasi Penggunaan Antidiabetes pada Pasien Rawat Jalan di RST Bhakti Wira Tamtama Semarang - Sikni Retno Karminingtyas (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2026)
Type 2 diabetes mellitus is a metabolic disorder characterized by persistent hyperglycemia exceeding normal values of 126 mg/dl due to impaired insulin production in the human body. The purpose of this study was to evaluate the appropriateness of antidiabetic medication use in outpatients with type 2 diabetes mellitus at Bhakti Wira Tamtama Hospital for the period January–June 2024. This study was a descriptive study with a retrospective approach. The sampling technique used a purposive sampling method, with 100 patients. Data were analyzed based on the 2021 PERKENI and 2021 edition of DIH guidelines. The majority of type 2 diabetes mellitus patients at Bhakti Wira Tamtama Hospital were female (56%) and aged 56–65 years (66%). The most commonly used single antidiabetic medication was glimepiride (20%), a combination of two drugs glimepiride and metformin (16%), and a combination of three drugs acarbose + gliclazide + metformin (5%). The evaluation of antidiabetic medication use included 100% accuracy in indications, 100% accuracy in patients, 61% accuracy in drugs, and 100% accuracy in doses. Overall, the evaluation of antidiabetic medication use at Bhakti Wira Tamtama Hospital averaged 90.25%.